2009
DOI: 10.3168/jds.2008-1951
|View full text |Cite
|
Sign up to set email alerts
|

Restricting daily time at pasture at low and high pasture allowance: Effects on pasture intake and behavioral adaptation of lactating dairy cows

Abstract: In pasture-based dairy systems, daily time at pasture is restricted during several periods of the year. The aim of this experiment was to evaluate the effect of restricting time at pasture on milk yield, pasture dry matter (DM) intake, and grazing behavior of dairy cows according to pasture allowance (PA), which partly defines pasture availability. The experiment was carried out in spring on strip-grazed perennial ryegrass pastures. The 6 treatments consisted of 3 durations of daily time at pasture [U: unrestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 14 publications
5
27
2
4
Order By: Relevance
“…Animals with full-time access to pasture (22H) only spent 0.36 of their time grazing at pasture. These results are comparable to the results achieved by Kennedy et al (2009) and Pé rez-Ramírez et al (2009). Iason et al (1999) have shown that regardless of food availability, sheep with restricted pasture access grazed for almost all of the available grazing time by grazing for fewer, longer foraging bouts, but still had a much shorter total grazing time than sheep with continuous access to pasture.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Animals with full-time access to pasture (22H) only spent 0.36 of their time grazing at pasture. These results are comparable to the results achieved by Kennedy et al (2009) and Pé rez-Ramírez et al (2009). Iason et al (1999) have shown that regardless of food availability, sheep with restricted pasture access grazed for almost all of the available grazing time by grazing for fewer, longer foraging bouts, but still had a much shorter total grazing time than sheep with continuous access to pasture.…”
Section: Discussionsupporting
confidence: 77%
“…It is possible that the results achieved by Pé rezRamírez et al (2009) and Kristensen et al (2007) were due to the fact that animals were given access to pasture in one continuous block rather than dividing the time into two distinct periods. Kennedy et al (2009) andPé rez-Ramírez et al (2009) have previously shown that when access time to pasture is split into two distinct periods for cows with restricted access, there is no effect on DMI and milk production when compared with cows grazing full time.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been reported that, with lowto-medium supplementation levels, MY is generally reduced when daily time at pasture, given in one grazing session daily, is ,8 h (Kristensen et al, 2007;Delaby et al, 2008). It is clear that dairy cows can react to a time constraint at grazing through an increase in the proportion of time spent grazing and in PI rate (Kennedy et al, 2009;Pé rez-Ramírez et al, 2009). In these studies, with restricted access time, 90% to 95% of time is spent grazing and PI rate can increase by 30% to 40% when compared to full-time grazing.…”
Section: Variation Of Nutrient Supply At Grazing Relative To Animal Rmentioning
confidence: 99%
“…To maximise cow behavioural adaptation and grazing efficiency, it can be recommended to split access time into two sessions per day, that is, after milking times, particularly at low supplementation level where high PI is expected. In fact, cows seem unable to maintain a high rate of grazing activity during one daily grazing session of 8 to 9 h (Pé rez- Ramírez et al, 2009;Pé rezPrieto et al, 2011), but can maximise proportion of time spent grazing and PI rate during two grazing sessions of 3 to 4 h (Kennedy et al, 2009;Pé rez-Ramírez et al, 2009). PA or sward height, partly determining PI rate, have also been shown to affect the ability of ruminants to adapt to a time constraint (Pé rez-Ramírez et al, 2009).…”
Section: Variation Of Nutrient Supply At Grazing Relative To Animal Rmentioning
confidence: 99%
“…Studies conducted in conventional pasture-based systems have analyzed the impact of supplementation (Phillips and Leaver, 1986;Sheahan et al, 2011), frequency of pasture allocation (Dalley et al, 2001;Granzin, 2003), pasture height (Gibb et al, 1997) and pasture allowance (Chilibroste et al, 2012), together with available grazing time (Gregorini et al, 2009;Kennedy et al, 2009;Perez-Ramirez et al, 2009), prior fasting (Chilibroste et al, 1997 and2007) and time of the day (Gregorini, 2012) on cow behavior.…”
Section: Introductionmentioning
confidence: 99%